Prevalence of Ehrlichia canis in Canis familiaris at Fauna Veterinary Services and Pegasus Veterinary Clinic in the city of Bogotá - Cárdenas Navarrete, María Juliana; Díaz Useche, Juvenal Felipe; Molano Pérez, Diana Patricia (Spei Domus, 2025)
Introduction: Canine ehrlichiosis is a disease caused by the intracellular bacterium Ehrlichia canis, transmitted by the tick Rhipicephalus sanguineus, with a prevalence in warm regions of Colombia and sporadic cases in Bogotá linked to travel to these areas. Methodology: This retrospective descriptive cross-sectional study analyzed 68 clinical records of dogs seen between 2019 and 2021 at two veterinary clinics in Bogotá (Servicios Veterinarios Fauna and Clínica Veterinaria Pegasus). Epidemiological variables (sex, age, breed, origin, travel to warm zones) and clinical variables (symptoms and hematological alterations) were evaluated to confirm infection via rapid tests (SNAP 4Dx, BIONOTE) and to correlate findings with clinical signs and laboratory results. Results: The overall prevalence was 35.29%, with a higher incidence in adult females of small and medium breeds, particularly Schnauzers and mixed breeds. A significant association was found with travel to warm areas such as Tolima and Meta, and predominant hematological findings included leukopenia (50%), anemia (33%), and thrombocytopenia (28%). Common clinical signs included fever, depression, weight loss, and pale mucous membranes, reflecting the bacterium’s tropism for white blood cells. Conclusion: This study underscores the importance of clinical and laboratory diagnosis for managing the disease despite limitations in advanced testing and highlights the need for vector control strategies and epidemiological surveillance, considering the zoonotic potential and the vector’s adaptability to urban areas.